Hyperglycemia-mediated onset of myocardial insulin resistance – unraveling molecular mechanisms and identifying therapeutic targets - Joseph, Danzil Eugene (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.